Analysis of the car body stability performance after coupler jack-knifing during braking. Issue 6 (3rd June 2018) - Guo, Lirong; Wang, Kaiyun; Chen, Zaigang; Shi, Zhiyong; Lv, Kaikai; Ji, Tiancheng
ABSTRACT: This paper aims to improve car body stability performance by optimising locomotive parameters when coupler jack-knifing occurs during braking. In order to prevent car body instability behaviour caused by coupler jack-knifing, a multi-locomotive simulation model and a series of field braking tests are developed to analyse the influence of the secondary suspension and the secondary lateral stopper on the car body stability performance during braking. According to simulation and test results, increasing secondary lateral stiffness contributes to limit car body yaw angle during braking. However, it seriously affects the dynamic performance of the locomotive. For the secondary lateral stopper, its lateral stiffness and free clearance have a significant influence on improving the car body stability capacity, and have less effect on the dynamic performance of the locomotive. An optimised measure was proposed and adopted on the test locomotive. For the optimised locomotive, the lateral stiffness of secondary lateral stopper is increased to 7875 kN/m, while its free clearance is decreased to 10 mm. The optimised locomotive has excellent dynamic and safety performance. Comparing with the original locomotive, the maximum car body yaw angle and coupler rotation angle of the optimised locomotive were reduced by 59.25% and 53.19%, respectively, according to the practical application. The maximum derailment coefficient was 0.32, and the maximum wheelset lateral force was 39.5 kN. Hence, reasonable parameters of secondary lateral stopper can improve the car body stability capacity and the running safety of the heavy haul locomotive.